Dampak Biaya Pinjaman, Persyaratan Agunan, dan Faktor Sisi Penawaran Terhadap Inklusi Keuangan Usaha Mikro di Tanggetada - Maya, Ade; Kumalasari, Fitri; Zul Bay, Agus (Universitas Pahlawan Tuanku Tambusai, 2025)
This research explores the influence of loan costs, collateral requirements, and supply-side factors on financial inclusion among micro-enterprises in Tanggetada District. Utilizing a quantitative approach, data were gathered through questionnaires from 227 micro-business owners, incorporating both primary and secondary sources. The results reveal that all three factors have a positive and significant impact on financial inclusion. Consequently, financial institutions should reconsider their policies on loan costs and collateral requirements to better accommodate the needs of micro-enterprises, ensuring broader access to financial services. Additionally, the Cooperative Office plays a vital role in supporting micro-entrepreneurs by enhancing their financial literacy and access to formal financial services, ultimately fostering business growth and sustainability.